PENTINGNYA MENERAPKAN PELATIHAN KERJA PEGAWAI DALAM MENINGKATKAN KINERJA PEGAWAI PADA KANTOR BAPPEDALITBANG KOTA PALANGKA RAYA - Toendan, Rita Yuanita; Hansly, Hansly; Peridawaty, Peridawaty (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
Community service is carried out to improve performance in the field of human resources in the regional apparatus organization at the Palangka Raya City Bappeda office. It is necessary to provide job training in improving performance, as a motivation so that employees feel confident in completing tasks. To get the appropriate results, it was analyzed by distributing a questionnaire to 40 employees, to draw conclusions. The results of the service show that there is a need for job training by providing work motivation to increase employee job satisfaction.